Avaliação da resistência mecânica do solo à penetração na microbacia D Núcleo Cunha - SP - Rodrigues, Valdemir Antonio [UNESP]; Masiero, Fabrício Campos [UNESP]; Daronco, Camila [UNESP]; Navarro, Everton Chequeto [UNESP]; Carvalho, José Luiz de (My University, 2012)
This study aimed to evaluate the mechanical resistance of soil penetration with a penetrometer in Red Yellow dystrophic Latosol, in following relief watershed riparian zone of the watershed. The environment is located in the State Park of Serra do Mar - Center Cunha, Sao Paulo State, Brazil. Measurements were taken at five different distances from the watercourse, and the riparian zone: 15 and 30 m from the river, in the hillside: 50 and 100 m, and on the slope near the watershed at 150 m from the river. These sites were five measurements of the mechanical resistance to penetration, in the layers: (0,0 a 0,1), (0,1 a 0,2), (0,2 a 0,3), (0,3 a 0,4), (0,4 a 0,5) e (0,5 a 0,6) meters deep, with manual penetrometer, model DIK -5520, serial No. 0456, with a capacity of 25 kgf.cm-2. Through the results it was concluded that the riparian zone the average strength of soil penetration resistance ranged from 00 to 0,96 MPa, whilethe hillside and the slope was a variation from 00 to 1,94 MPa and 00 to 1,35 Mpa, respectively. In the riparian zone to 30 m away from the river, the forces were observed more intense in the deeper layers to 0,60 m, while the hillside to 50 and 100 meters away, the larger forces were observed in layers 0,30, 0,50 and 0,60 meters in depth. In the range of 0,10 m depth there was no significant difference in soil penetration resistance in the five distances from the river, which indicates that there is no compaction of the soil surface from thesplitter to the riparian zone, which facilitates water infiltration into the soil and consequently reduce the runoff of rainfall, resulting in greater conservation of the watershed.

O presente trabalho teve por objetivo avaliar a resistência mecânica do solo à penetração com um penetrógrafo, em Latossolo Vermelho-Amarelo, distrófico, fase rasa, na toposequência do relevo do divisor de águas à zona ripária da microbacia. O ambiente fica localizado no Parque Estadual da Serra do Mar – Núcleo Cunha, Estado de São Paulo, Brasil. Foram realizadas medições em cinco diferentes distâncias do curso d’água, sendo na zona ripária: 15 e 30 m do rio, na meia encosta: 50 e 100 m, e, na encosta próximo do divisor de águas a 150 m do rio. Nestes locais foram realizadas cinco medições da resistência mecânica do solo à penetração, nas camadas de: (0,0 a 0,1), (0,1 a 0,2), (0,2 a 0,3), (0,3 a 0,4), (0,4 a 0,5) e (0,5 a 0,6) m de profundidade, com penetrógrafo manual, modelo DIK-5520, serial n°0456, com capacidade de 25 kgf.cm-2. Através dos resultados concluiu-se que nas parcelas da zona ripária a força média de resistência do solo à penetração variou de 0 a 0,96 MPa, enquanto que na meia encosta e na encosta houve uma variação de 0 a 1,94 MPa e de 0 a 1,35 MPa, respectivamente. Na zona ripária a 30 m de distância do rio, as forças mais intensas foram observadas nas camadas mais profundas a 0,60 m; enquanto na meia encosta a 50 e 100m de distância, as maiores forças foram observadas nas camadas de 0,30, 0,50 e 0,60 m de profundidade. Na faixa de 0,10 m de profundidade não houve diferença significativa da resistência a penetração no solo, nas cinco distâncias do rio, onde não há compactação superficial do solo desde o divisor até a zona ripária, o que facilita a infiltração da água no solo e, conseqüentemente diminui o escoamento superficial da água das precipitações, resultando em maior conservação da microbacia.
Resistance evaluation of soil penetration of the division of waters to riparian zone the watershed D Núcleo Cunha - SP
Keywords: Mechanical resistance; Penetrometer; Watershed; Resistência mecânica; Penetrógrafo; Microbacia